The Effect of Work Boredom and Self-Control on Cyberloafing Behavior - Nur Rohmah, Selfi; Risdianto, Risdianto; Laelatul Qodriah, Sari (Ann Publisher, 2024)
In this study, there are variables X1 (Work Boredom), X2 (Self Control), and Y (Cyberloafing Behavior). This research was conducted to determine (1) The Effect of Work boredom on Cyberloafing Behavior. (2) The Effect of Self Control. (3) Effect of Work Boredom and Self Control on Cyberloafing Behavior. The approach used in this study is descriptive quantitative. The population used in this study is 37 employees at CV. JSA Management Jakarta using census samples. The primary and secondary data were collected through observation, interviews, and questionnaires. The measurement scale in this study uses a Likert scale. The analysis techniques used are the validity and reliability test, multiple linear regression test, coefficient of determination test, T-test, and F test. The results show that (1) Work boredom has a significant effect on cyberloafing behavior, and (2) Self-control has a significant negative effect on cyberloafing behavior, (3) Work boredom and self-control simultaneously influence cyberloafing behavior.